Effect of Past Coworkers on Job Search Evidence from Austria - Michèle Weynandt; Perihan Saygin; Andrea Weber (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
This paper evaluates the strength of information flow from employed past coworkers on the re-employment duration of displaced workers due to plant closures in Austria. Using the Austrian Social Security Database (a matched employer-employee database) we exploit the panel structure of 36 years of data to construct the network of past coworkers. The paper also evaluates the probability to drop out of labor force as well as subsequent match quality based on re-entry wages and re-entry tenure. We find that a 10 percentage point increase in the network employment rate leads to a 3.2 percent increase in the exit hazard from unemployment, and to a 2.5 percent decrease in the drop out hazard. It is also associated with a 0.5 EUR increase in the daily re-entry wages and a 0.4 percentage point increase in the probability to have tenure of at least a year. Additionally, we find a significant difference between males and females.
Keywords: J63; J64; J65; 330